1972
DOI: 10.2105/ajph.62.7.909
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution, climate, and home heating: their effects on U.S. mortality rates.

Abstract: The aim of this report is to determine whether changes in air pollution have an effect on health. Climate and home heating variables are included to see whether they may be involved. These studies indicate a close association between mortality rates and air pollution and lead to the conclusion that mortality rates could be lowered by abating pollution. Estimates of economic benefits from improved health are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1976
1976
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Ten studies were ecologic or time series (Bobak and Leon 1992; Chay and Greenstsone 1999 Chay and Greenstsone 2003; Ha et al 2003; Joyce et al 1989; Knöbel et al 1995; Lave and Seskin 1972; Loomis et al 1999; Penna and Duchiade 1991; Sinkura et al 1999), two were cross-sectional (Hunt and Cross 1975; Lipfert et al 2000), two were cohort studies (Gehring et al 2002; Woodruff et al 1997), and one a matched case–control study (Bobak and Leon 1999b). All used area-based estimates of air pollution exposure, except for the German study, which used a Geographic Information Systems model to provide individual ambient pollution estimates (Gehring et al 2002).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten studies were ecologic or time series (Bobak and Leon 1992; Chay and Greenstsone 1999 Chay and Greenstsone 2003; Ha et al 2003; Joyce et al 1989; Knöbel et al 1995; Lave and Seskin 1972; Loomis et al 1999; Penna and Duchiade 1991; Sinkura et al 1999), two were cross-sectional (Hunt and Cross 1975; Lipfert et al 2000), two were cohort studies (Gehring et al 2002; Woodruff et al 1997), and one a matched case–control study (Bobak and Leon 1999b). All used area-based estimates of air pollution exposure, except for the German study, which used a Geographic Information Systems model to provide individual ambient pollution estimates (Gehring et al 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Most reviewed studies used total suspended particulates (TSP) (Bobak and Leon 1992, 999b; Chay and Greenstone 1999, 2003; Ha et al 2003; Hunt and Cross 1975; Joyce et al 1989; Lave and Seskin 1972; Penna and Duchiade 1991; Shinkura et al 1999), PM 10 (Lipfert et al 2000; Woodruff et al 1997), or PM 2.5 (Gehring et al 2002; Loomis et al 1999) as measures of exposure to PM. One study used visibility as a measure of particulate air pollution (Knöbel et al 1995).…”
Section: Methodsmentioning
confidence: 99%
“…To determine the level of attribute, we referred to many previous studies conducted on similar issues. According to Lave and Seskin's (1979) report, if sulfate, which is one of the types of air pollutants, increases by 1 mg/m 3 , the total mortality rate would increase by 6.7 per 100,000 persons. Moreover, Kim (1991) found that if the air pollutants increased by 10%, the total mortality rate would increase by 29 per 100,000 persons.…”
Section: Mortalitymentioning
confidence: 99%
“…At the western end of Oakland, the Graduate School of Public Health at the University of Pittsburgh, a leading institution in the epidemiology of air pollution, was home to nationally known air pollution researcher Morton Corn (Corn and Demaio, 1964;Antommaria et al, 1965;Corn and Montgomery, 1968). A few city blocks east of Oakland was Carnegie Mellon University (known as Carnegie Institute of Technology before 1967), where Lester B. Lave and Eugene Seskin turned out a series of nationally recognized articles on air pollution and human health (Lave and Seskin, 1970a,b, 1972, 1973Lave and Omenn, 1981). Many of these researchers, including Lave, also belonged, as private citizens, to a local environmental action organization formed in 1969 and known as the Group Against Smog and Pollution, or GASP (Longhurst, 2004).…”
Section: Case Study: Allegheny Countymentioning
confidence: 99%